Flocculation performance and mechanism of chitosan-based flocculants in the treatment of emulsified oily wastewater. Issue 7 (3rd July 2017) - Zhang, Shuang; Lü, Ting; Qi, Dongming; Zhao, Hongting
ABSTRACT: Chitosan (CS)-based flocculants, denoted as CS-g-PAM and CS-g-PDBC, were successfully prepared via graft copolymerization of CS with acrylamide (AM) or dimethyl acryloyloxyethyl benzyl ammonium chloride (DBC). The grafting was confirmed by Fourier transform infrared spectroscopy (FTIR) and x-ray photoelectron spectroscopy (XPS). The flocculation performance of CS-g-PAM and CS-g-PDBC, as well as flocculants such as cationic polyacrylamide (CPAM), polyaluminum chloride (PAC), and CS, was evaluated and compared for treating emulsified oil wastewater. It was found that CS-g-PDBC exhibited excellent flocculation performance under both acidic and neutral conditions, while CS showed better flocculation ability under alkaline condition. The flocculation mechanism of CS and CS-g-PDBC was investigated via zeta potential measurements. Results showed that different flocculation mechanisms were involved at various pH levels. As regarding CS, the flocculation mechanism is mainly charge neutralization, patching, and sweep floc under acidic, neutral, and alkaline conditions, respectively, while for CS-g-PDBC, patching was the dominant mechanism under both acidic and neutral conditions. GRAPHICAL ABSTRACT: